Ile na głowie miała Maria Konopnicka? Synteza w projektach Wojtka Janikowskiego na podstawie okładki „Dezorientacje. Biografia Marii Konopnickiej” Magdaleny Grzebałkowskiej - Bizior, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article presents an analysis of the cover of Magdalena Grzebałkowska’s Dezorientacje. Biografia Marii Konopnickiej (Disorientations. The Biography of Maria Konopnicka) (published by Znak in 2024) in relation to the works of Wojtek Janikowski and in the context of the covers of contemporary biographies and personal letters of famous Polish writers and artists (including Agnieszka Pasierska’s designs for the “Biografie” series by Czarne and Ana Pol’s designs for the biographies published by Marginesy.) The starting point for Janikowski’s project is the juxtaposition of the poet’s photograph with a collage of various elements related to her life and work which were used to form the top of her hat. The cover of Magdalena Grzebałkowska’s book is not only a synthetic take on Maria Konopnicka’s biography and work, but also a comprehensive and varied vision of women's life in the second half of the 19th century. The article presents an analysis of all the elements that Janikowski placed on the poet’s hat which introduce us into the area of associations related to Konopnicka’s life and work (flowers, animals, train, travel case, the Eiffel Tower, penny-farthing, book, corset, sabre, krasnal).